The inverted classroom in health care - learner in the focus of digital change. Contribution to the HoGe conference 2018 "Digital learning and teaching" / Der Inverted Classroom in den Gesundheitsberufen - Lernende im Fokus des digitalen Aufbruchs. Beitrag zur HoGe-Tagung 2018 "Digitales Lernen und Lehren" - Gloerfeld Christina; Felgentreu Jessica; Witt Claudia de (Sciendo, 2019)
Digitization demands specific professional skills to meet current and future requirements. Especially in health professions, stakeholder are faced with the challenge to keep up with technological developments and changes in working structures, learning and communication processes. In addition, there is a need to modernize qualification structures and to beter connect theory and practice. The Inverted Classroom Model (ICM) provides a promising conceptual framework to approach these tasks systematically and provides suitable starting points to be integrated into existing structures. The ICM swappes classic teaching and learning spaces and links them using digital media. Thus there is more space and time, to create, to learn independently and to cooperate. This article presents the development and implementation of an ICM for the training of speech therapists and further training of hygiene professionals, based on their demands. Thereby conditions of success are derived. For this purpose, the results from two evaluations are stated - a target group analysis (standardized questionnaire) and the testing of the technical and media pedagogical implementation (focus groups). The results of the standardized survey provided a heterogeneous picture of the experiences in coping with digital media and clarified the need for practice-oriented and flexible learning opportunities. Based on this, a learning platform with appropriate communication and learning tools as well as learning content was developed. In focus groups, strengths and weaknesses of the implementation were identified, which led to technical and didactical adjustments. Due to the strong target group orientation, significant added value could be generated, which leads to higher acceptance, and is the prerequisite for sustainable integration. With the ICM it is possible to initiate active learning processes in both target groups and to establish a fruitful relationship between theoretical knowledge and practical experience.